PERANCANGAN SILINDER HIDROLIK PADA MESIN MOLDING KARET DENGAN KAPASITAS 25 TON - Muhammad Al Haramain; Riki Effendi; Harmanung Adi Susilo (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2017)
The hydraulic system has been widely used for various tools. The system developed from Pascal's law becomes one of the vital knowledge that its use in the industrial world. Ranging from small businesses to some kind of a car wash with large industries such as molding machine. The components are arranged in the hydraulic cylinder includes a tube, piston, rod axles, gland, and seal. Each component has the function and role of each and every component seal types are also different types, for a material component of the hydraulic cylinder must not rustproof for hydraulic oil in addition to the driving also serves to lubricate the hydraulic cylinder components. The greater the pressure in the hydraulic tube is getting thicker the hydraulic tube wall, so that the seal does not leak type of profile and material must be in accordance with the state of the hydraulic cylinder, for the connection technique in the hydraulic cylinder components should also be considered such as when welding, welding wire material must be in accordance with the material to be welded. For the methods used in the design of the hydraulic cylinder on the rubber molding machine is an analytical method burdened straight column in the center of axle rodmethods MAWP (Maximum Allowable Working Pressure) to force the tube The results of this design is for a straight column burden in the short-sized center, and to the strength of the tube can withstand the pressure 607.74 bar as well as the costs required to make the hydraulic cylinders in rubber molding machine is very affordable.